Development of a neighborhood drivability index and its association with transportation behavior. (30th September 2020) - den Braver, N R; Lakerveld, J; Gozdyra, P; van de Brug, T; Moin, J S; Fazli, G; Brug, J; Moineddin, R; Beulens, J W J; Booth, G L
Abstract: Background: To develop and validate a drivability index for the City of Toronto and examine its association with transportation mode choice. Methods: We used exploratory factor analysis to derive distinct factors (clusters of one or more environmental characteristics) that reflect the degree of car dependency in each neighborhood, drawing from candidate variables that capture density, diversity, design, destination accessibility, distance to transit, and demand management. Area-level factor scores were then combined into a single composite score, reflecting neighborhood drivability. Negative binomial generalized estimating equations were used to test the association between driveability quintiles (Q) and primary travel mode (>50% of trips by car, public transit, or walking/cycling) in a population-based sample of 63, 766 Toronto residents enrolled in the Transportation Tomorrow Survey (TTS), adjusting for individual and household characteristics, and accounting for clustering of respondents within households. Results: The drivability index consisted of three factors: Urban sprawl, pedestrian facilities and parking availability. Relative to those living in the least drivable neighborhoods (Q1), those in high drivability areas (Q5) had a significantly higher rate of car travel (adjusted rate ratio (RR):1.80, 95%CI:1.77-1.88), and lower rate of public transit use (RR:0.90, 95%CI:0.85-0.94) and walking/cycling (RR:0.22, 95%CI:0.19-0.25). Associations were strongest for short trips (<3 km) and in analyses where both residential and workplace drivability was considered (RR for car use in high/high vs. low/low residential/workplace drivability: 2.18, CI:2.08-2.29). Conclusions: This novel neighborhood drivability index predicted whether local residents drive or use active modes of transportation and can be used to investigate the association between drivability, physical activity, and chronic disease risk. Key messages: The association between neighborhood drivability and car use was strongest for short trips. The drivability of the neighborhood where people work is a strong determinant of car use.